Analisis Dan Perancangan Sistem Informasi Lingkungan Perumahan Dengan Metode Waterfall Berbasis Web Pada Perumahan Puri Adika Bogor - Wahyudi, Erwin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
The Puri Adika Bogor Residential needs fast, clear and efficient access to information, both for data collection, payment of fees and social activities. The current information dissemination done through WhatsApp group messages managed by the housing management. The dissemination of information considered less effective because the history of information sent through WhatsApp group messages was easily deleted and replaced by many incoming messages. The information system designed to minimize these barriers are web-based, using information system design based on the Waterfall method. The Waterfall method considered suitable for designing information systems that more effective and can produce that system into well organized and documented. This system also systematically created and managed so that each transaction can be properly recorded in detail. The integration between all management activities of Puri Adika Bogor Residential can be seen through the application in the menus listed on the main dashboard page including Resident Menu, MSMEs, Events, Resident Fees, Expenses and Reports. The results of black box testing conducted show that this web-based application can be used and provides satisfactory results. The results of the comparison of the difference between the current state and the state after the improvement show that with this web-based application the record keeping system is more efficient.